Clinical case: Nursing care of an inmate with thoracic window - MC Martín-Cocinas Fernández; G Peñuelas-Olivo (Sociedad Española de Sanidad Penitenciaria, 2019)
ABSTRACT Objective: To make a comprehensive assessment of a pacient who has a thoracoscopy or thoracic window that needs wound care. Through the functional patterns of Marjory Gordon and the NANDA taxonomy (North American Nursing Diagnosis Association), NIC (Nursing Interventions Classification), and NOC (Nursing Outcomes Classification). As well as helping the healing and closing time of the wound to be shorter, reducing the risk of infection and improving the quality of life of the patient. Case presentation: The clinical case of the patient with thoracic window is described. The real and potential diagnoses were established, some objectives or NOC were set and the necessary activities or NIC were carried out to reach them. Results: On a Likert scale (1 to 5), a wound healing was obtained, from 1 to 3, a level of anxiety, from 3 to 4, a problem coping, from 3 to 4, a level of self-care, from 2 to 4, the promotion of health, from 2 to 4, and the therapeutic regimen, from 2 to 4, after one year of follow-up. Conclusions: The comprehensive approach that should be performed to the patient, not focused only on the reason for the consultation, but assessing the different functional patterns to know which are altered and take into account the evolution of the process and better care and quality improvement of the patient's life.